ANALISIS HUKUM ATAS UPAYA PENGAJUAN PASPORDENGAN MELAMPIRKAN DOKUMEN PALSU SEBAGAIPERSYARATAN DATA KEPENDUDUKAN - Deky Aprian (2021)
In the use of travel documents of the Republic of Indonesia in practice there are still many that are misused by their holders, thus causing a threat to the Indonesian state originating from outside the territory of Indonesia. The purpose of this study was to determine the criminal law enforcement process for attempts to use fake residence documents in the passport application process at the Immigration Office. This research is empirical normative research. A conclusion was reached Immigration law is part of the positive legal rules that exist in Indonesia and is part of state administrative law that runs government in a narrow sense. The essence of immigration itself, is a series of activities in the provision of services and law enforcement as well as safeguarding traffic in and out of people from and into the territory of the Republic of Indonesia, as well as monitoring the presence of foreign nationals in the territory of the Republic of Indonesia The provisions of the Immigration Law confirm that Immigration officials have the right to refuse a person to leave Indonesia's territory in the event that the person does not have a valid travel document and is still valid. Several legal provisions that can be used to ensnare perpetrators of document forgery in making passports, including the provisions of the Criminal Code (KUHP) and legal provisions contained in the immigration laws and regulations.